2012
DOI: 10.1590/s0102-09352012000200026
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de componentes de (co)variância para peso e escores visuais de conformação frigorífica em bovinos Nelore

Abstract: Estimativas de componentes de (co)variância para peso e escores visuais de conformação frigorífica em bovinos Nelore RESUMOEstimaram-se os componentes de (co)variância e herdabilidade da conformação frigorífica à desmama (CFD), conformação frigorífica ao sobreano (CFS), peso à desmama (PD) e peso ao sobreano (PS) de animais Nelore, e as correlações genéticas entre essas características. Um modelo animal multicaracterística foi proposto para analisar 6.397 informações de peso e escores visuais de conformação fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Wenceslau et al (2012) em bovinos da raça Nelore. Tendo em vista que os animais do presente estudo foram mantidos em regime de criação a pasto, esse valor pode ser considerado satisfatório.…”
unclassified
“…Wenceslau et al (2012) em bovinos da raça Nelore. Tendo em vista que os animais do presente estudo foram mantidos em regime de criação a pasto, esse valor pode ser considerado satisfatório.…”
unclassified
“…Higher heritability estimates were reported by Barichello et al (2010) in Canchim cattle for the same trait, which was assessed at weaning, and varied from 0.17 to 0.27. Heritability estimates for other visual score assessments in Nellore and Angus herds obtained at the weaning and yearling stages have ranged from 0.19 to 0.38 (Cardoso et al, 2004;Boligon and Albuquerque, 2010;Faria et al, 2009Faria et al, , 2010Koury Filho et al, 2010;Boligon et al, 2012;Wenceslau et al, 2012). These differences in heritability estimates could be caused by differences in the definition of visual assessment scores, the model applied to estimate the (co)variance components, as well as to differences in genetic and environmental variability between the populations or herds studied.…”
Section: Resultsmentioning
confidence: 99%
“…Barichello et al (2010) also reported moderate (0.61) and low (0.17) genetic correlation estimates between slaughter conformation scores and live weight and scrotal circumference at weaning, respectively, in Canchim animals. Recently, Wenceslau et al (2012), working with Nellore cattle, obtained positive and moderate to high genetic correlation estimates that ranged from 0.61 to 0.81 between growth traits (weight at weaning and yearling) and slaughter conformation scores at weaning and yearling. The results obtained in the present study suggest that selection to increase yearling weight would improve carcass conformation and composition.…”
Section: Resultsmentioning
confidence: 99%
“…For the assessmet of Slick Hair mutation, carcass traits were collected by ultrasonography measurements in the Longissimus dorsi muscle between the 12 th and 13 th ribs: ribeye area in squared centimeters (REA), backfat thickness in millimeters (BF) and intramuscular fat expressed in percentage (IMF). In addition, in relation to carcass the score carcass conformation (SCC) described by Wenceslau et al (2012), as a visual assessment in scores of (1 -6) for precocity, muscularity, and structure was used. As growth trait was assessed weight (YW) expressed in kilograms (kg), and as precocity trait the scrotal circumference (SC) in centimeters (cm).…”
Section: Slick Hair Analysismentioning
confidence: 99%
“…and intramuscular fat expressed in percentage (IMF). In addition, in relation to carcass the score carcass conformation (SCC) described by Wenceslau et al (2012) as a visual assessment in scores of (1 -6) for precocity, muscularity, and structure was used. As growth trait was assessed weight (YW) expressed in kilograms (kg), and as precocity trait the scrotal circumference (SC) in centimeters (cm).…”
Section: Traitsmentioning
confidence: 99%